The Effect of Smartphone Testing and Computerized Testing on Third Grade Students Biology’ Acceleration in Teaching Methods of Science and Teaching Techniques - Abdullah Salman, Salim (Opción, 2019)
Most educational institutions in Iraq suffer from the typical exams, which may not be the true measure of the level of the student, and questions placed in a traditional way does not stimulate the student to think and answer, which is supposed to be the result of understanding the perception of relationships be- tween cognitive experiences, which will be the most answers based on Preser- vation and retrieval of material that leads to some students or perhaps many of them to cheat in some way, in addition to that the paper examinations require great potential to achieve its objectives, it requires specialized staff to create all the appropriate conditions for the performance of exams Represented by various committees such as (Examination Committee), (Correction Commit- tee), (Audit Committee), (Supervisory Committee), (Observer Committee) and (Monitoring Committee of grades), and despite all these committees many problems and errors lead to some injustice In the results of students, this leads to many objections by students at different stages and grades for different subjects in general and scientific subjects in particular in addition to the delay in giving results that may take weeks or more, on the other hand, the reasons and necessities of university teaching Develop curriculum elements and intro- duce technology components To teach in the joints of the main institutions of education in general and in the field of teaching and education in particular it became imperative to adopt methods and methods and tools of assessment and evaluation commensurate with the inputs and outputs of university preparation that emphasizes the development and improvement of knowledge and skills expertise through the adoption of modern tech- nological education technology, but we are still despite all The successes and positive results achieved by educational technology at the Arab and global levels are far from the optimal and successful use of this technolo- gy, despite the existence of some simple attempts, specifically the evalua- tion methods and evaluation that are supposed to Fit what let him modern theories of education and learning, it may be the reason not to use modern technology in several technical reasons for university assessment includ- ing the following:1- Weaknesses and shortcomings in the preparation of teaching staff trained on the use of electronic evaluation programs. 2 - Weak activation of technical training activities and technology for stu- dents in different stages of study. 3 - lack of potential and lack of alternatives to test the large numbers of students. 4 - Recent experiences are unfamiliar because they do not fit the educa- tional systems in Iraqi educational institutions. 5 - risk that may cause chaos or cheating when using electronic education- al technology in the field of tests. 6 - the quality of scientific study materials, specialized or educational, which is difficult to conduct according to electronic technology, especially materials that rely on explanation or article or derivative equations. 7 - the multiplicity of quality of electronic tests and the diversity of its pro- gramming is difficult for the teaching to deal with them in the same way, especially electronic tests for different educational platforms and tests of smart phones. 8 - Most of the electronic tests need special preparation, the most impor- tant of which is the provision of the Internet and a computer and this does not fit with the exam instructions, which stresses the lack of the introduc- tion of smart phones and cut off the Internet. For all the reasons above and others that can not be limited in this research we find that there is an urgent and urgent need to conduct a research to identify the obstacles and difficulties that can be diagnosed and overcome when using the technology of instructional technology in formal or in- formal tests and identify the aspects or positive points envisaged from it, so this was The research is a necessity and an urgent need to answer the reasons mentioned above and through the use of two advanced electronic test techniques through the answer to the following question - What is the impact of the use of both smart phone tests and electronic tests (google classroom) on the speed of achievement of third grade stu- dents life sciences in the teaching methods and teaching techniques?